The U. S. Geological Survey National Hydrologic Model infrastructure: Rationale, description, and application of a watershed-scale model for the conterminous United States. (January 2019) - Regan, R.S.; Juracek, K.E.; Hay, L.E.; Markstrom, S.L.; Viger, R.J.; Driscoll, J.M.; LaFontaine, J.H.; Norton, P.A.
Abstract: The ability to effectively manage water resources to meet present and future human and environmental needs is essential. Such an ability necessitates a comprehensive understanding of hydrologic processes that affect streamflow at a watershed scale. In the United States, water-resources management at scales ranging from local to national can benefit from a nationally consistent, process-based watershed modeling capability to provide the requisite understanding. The National Hydrologic Model (NHM) infrastructure, which was developed by the U.S. Geological Survey to support coordinated, comprehensive, and consistent hydrologic modeling at multiple scales for the conterminous United States, provides this essential capability. NHM-based applications provide information to enable more effective water-resources planning and management, fill knowledge gaps in ungaged areas, and support basic scientific inquiry. In the future, as process algorithms and data sets improve, the NHM infrastructure will continue to evolve to better support the nation's water-resources research and management needs. Highlights: Nationally consistent, locally informed simulation of water budget components. Reduced initial costs for watershed studies using available models and data. NHM infrastructure is implemented with two model codes, potentially more in future. Flexible, open-source infrastructure that is extensible for research and operations. NHM-PRMS is available for the hydrologic community to download and use now.